Unconventional human CD61 pairing with CD103 promotes TCR signaling and antigen-specific T cell cytotoxicity - Hamid, Megat H. B. A.; Cespedes, Pablo F.; Jin, Chen; Chen, Ji-Li; Gileadi, Uzi; Antoun, Elie; Liang, Zhu; Gao, Fei; Teague, Renuka; Manoharan, Nikita; Maldonado-Perez, David; Khalid-Alham, Nasullah; et al. (Nature immunology, 2024)
Cancer remains one of the leading causes of mortality worldwide, leading to increased interest in utilizing immunotherapy strategies for better cancer treatments. In the past decade, CD103 + T cells have been associated with better clinical prognosis in patients with cancer. However, the specific immune mechanisms contributing toward CD103-mediated protective immunity remain unclear. Here, we show an unexpected and transient CD61 expression, which is paired with CD103 at the synaptic microclusters of T cells. CD61 colocalization with the T cell antigen receptor further modulates downstream T cell antigen receptor signaling, improving antitumor cytotoxicity and promoting physiological control of tumor growth. Clinically, the presence of CD61 + tumor-infiltrating T lymphocytes is associated with improved clinical outcomes, mediated through enhanced effector functions and phenotype with limited evidence of cellular exhaustion. In conclusion, this study identified an unconventional and transient CD61 expression and pairing with CD103 on human immune cells, which potentiates a new target for immune-based cellular therapies. CD103 + T cells are associated with control over tumors but how this is mediated is unclear. Here the authors show that CD61 colocalizes and functionally combines with CD103 in the T cell synaptic response to promote antitumor T cell responses.